Regulating the Algorithmic Panopticon: A Critical Library Research on Islamic Communication Policy and Digital Media Ethics in the Era of Hyperconnectivity - Ikhwansyah Nasution; Hasan Sazali; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
This study examines the ethical and regulatory challenges of hyperconnected digital media by integrating critical media theory with Islamic communication ethics. Using a critical textual-library methodology, the research analyzes scholarly literature, regulatory documents, digital policy texts, and Islamic normative sources related to algorithmic governance, post-truth communication, and public accountability. The findings show that traditional broadcasting regulation is increasingly inadequate because digital communication is now shaped by global platforms, OTT services, recommender systems, and algorithmic visibility. The study also finds that hyperreality and post-truth dynamics intensify ethical crises by allowing emotionally charged, divisive, and misleading content to gain influence through engagement-based amplification. In response, this article argues that Islamic principles such as tabayyun, qaulan sadida, amanah, and maslahah can provide a normative foundation for digital policy. The study proposes an ethical co-regulation model based on state oversight, civil society participation, platform transparency, algorithmic auditing, and freedom-of-expression safeguards to protect the digital public sphere. Its main contribution is a hybrid regulatory framework that links technological accountability with moral-spiritual responsibility in Islamic broadcasting